Hubungan Kebiasaan Konsumsi Fast Food dan Tingkat Stress dengan Siklus Menstruasi pada Mahasiswi Fakultas Ilmu Kesehatan Universitas Muhammadiyah Surakarta: The Correlation between Fast Food Consumption Habits and Stress Levels With Menstrual Cycle in Female Students Faculty of Health Sciences Universitas Muhammadiyah Surakarta - An Nuur Fadillah; Dyah Intan Puspitasari (Jurnal Diskursus Ilmiah Kesehatan, 2023)
Background: The high content of fatty acids in fast food can influence the body metabolism and may disturb the menstrual cycle. Meanwhile, in a state of stress, hormone in hypothalamus is stimulated that can disrupt the menstrual cycle. Aims: This study aimed to analyze the relationship between fast food consumption habits and stress levels with the menstrual cycle in female students of the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. Methods: The method used in this study was an observational study with a cross sectional study design. The sample used was 85 respondents using the simple random sampling technique. Data collection used a food frequency questionnaire (FFQ) to determine fast food consumption, Perceived Stress Scale-10 (PSS-10) to determine stress levels and a menstrual cycle questionnaire to determine the respondent's menstrual cycle. Results: 45% of respondents are often consume fast food, 27% of respondents experience high level of stress and 60% of respondents experience irregular menstrual cycles. The results were obtained from the analysis using Person Product Moment test which showed a value of p = 0.726 (P> 0.05) for fast food consumption with menstrual cycles and a value of p = 0.396 (p> 0.05) for stress levels with menstrual cycles menstruation. Conclusion: The conclusion of this study is that there is no significant relationship between fast food consumption and the menstrual cycle and there is no relationship between stress levels and the menstrual cycle in female students of the Faculty of Health Sciences, Universitas Muhammadiyah Surakarta. This research is expected to increase awareness of the need to consume healthy foods that are low in fat and sugar and maintain stress which are good for the health of young women, especially reproductive health.